Toxic levels of mercury for sequential larval stages of Macrobrachium rosenbergii (de Man) - Piyan, B.T.; Law, A.T.; Cheah, S.H. (Elsevier, 1985)
The toxicity of mercury for sequential stages of Macrobrachium rosenbergii (de Man) larvae was studied under static water conditions at a salinity of 12‰ and temperature of 25.5 - 27.0°C. The results revealed that stage 1 larvae had the lowest threshold lethal concentration (TLC) of mercury, 0.041 ppm Hg, while the post-larvae had a TLC of 0.325 ppm Hg. There was an abrupt increase in the TLC of mercury after the larvae had reached stage 5. The lower TLC prior to stage 5 is most probably due to the more frequent moulting and the relatively thinner cuticle of the larvae.